2022
DOI: 10.1002/er.7941
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the application of atomic layer deposition process for lithium‐ion based batteries

Abstract: Lithium-ion battery (LIB) systems provide a very promising range of power supply systems for diverse applications like electric vehicles, hybrid plug-in electric vehicles, grid storage systems, and microelectronics. Nevertheless, the features of lithium-ion batteries (LIBs), which include energy density and power, cycle lifetime, safety, as well as cost, must be enhanced in order to achieve all these feasible applications. Atomic layer deposition (ALD), as a result of its unique benefits above other thin-film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 200 publications
(341 reference statements)
0
8
0
Order By: Relevance
“…The ALD application relevance in the LIB field is confirmed by already available studies of cathode synthesis and its coating by atomic layer deposition method; [5][6][7][8][9] our team also analyzed the literature about ALD application for cathode coating, which consider many compositions of coatings and regularities associated with their synthesis. 4 Based on the review, the titanium oxide protective coating, on par with aluminum oxide, has revealed its efficiency in preserving cathode capacity at elevated current strengths, high cycling potentials, elevated temperatures and long-term cycling.…”
mentioning
confidence: 80%
“…The ALD application relevance in the LIB field is confirmed by already available studies of cathode synthesis and its coating by atomic layer deposition method; [5][6][7][8][9] our team also analyzed the literature about ALD application for cathode coating, which consider many compositions of coatings and regularities associated with their synthesis. 4 Based on the review, the titanium oxide protective coating, on par with aluminum oxide, has revealed its efficiency in preserving cathode capacity at elevated current strengths, high cycling potentials, elevated temperatures and long-term cycling.…”
mentioning
confidence: 80%
“…Li + jumps from one polymer chain to another, thus realizing the transmission of Li + . [50][51][52] However, ion conduction can also be performed by a unique crystal structure in the polymer electrolyte. Pairs of polyethyleneoxide (PEO) chains are folded together to form a cylindrical channel.…”
Section: Ion Transfer Mechanismmentioning
confidence: 99%
“…Driven by the electric field, Li + complexed/dissociated with the polymer segment, and moved from the coordination position to a new position, or at high temperature, the polymer produced free volume through local segment movement. Li + jumps from one polymer chain to another, thus realizing the transmission of Li + 50–52 . However, ion conduction can also be performed by a unique crystal structure in the polymer electrolyte.…”
Section: Interfacial Carrier Transportmentioning
confidence: 99%
“…Atomic layer deposition (ALD) has found applications in a variety of areas, including semiconductors, 1 membranes, 2 catalysts, 3 and batteries. 4 As a thin-film deposition technique with atomic-level precision, ALD is based on sequential selfterminating reactions between gaseous precursors and solid substrates. Therefore, ALD can deposit thin films with exceptional conformality and uniformity on even high-aspectratio structures at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%